Restorative practices and relational prison leadership in Ireland - Marder, Ian D. (Contemporary justice review, 2025)
The quality of relationships and levels of conflict are both critical elements of prison life, with consequences for people in custody, and for prison staff and leaders alike. This article presents findings from new research in which the Irish Prison Service’s senior leadership team received training in restorative practices: a set of principles and skills that aim to help professionals build relationships and address conflicts. We interviewed 22 leaders 3–5 months after their training to examine its self-reported effects on their thinking and practices. Respondents described adopting more relational communication approaches, using the principles and skills they had learned to de-escalate conflicts and to preserve or rebuild relationships with and among people in custody and colleagues. Arguing that a concept of relational prison leadership can help us develop and understand the connections between restorative practices, prison leadership practice, and prison social climates, the article makes both theoretical and empirical contributions to the nascent literatures on prison leadership and on restorative practices in prison settings.